Combination model of neutrophil to high-density lipoprotein ratio and system inflammation response index is more valuable for predicting peripheral arterial disease in type 2 diabetic patients: A cross-sectional study - Song, Yi; Zhao, Ying; Shu, Yan; Zhang, Liyin; Cheng, Wenzhuo; Wang, Li; Shu, Meng; Xue, Baorui; Wang, Ruonan; Feng, Ziyun; Yin, Yao; Yu, Fangyang; et al. (Frontiers in Endocrinology, 2023)
Neutrophil/high-density lipoprotein (HDL) ratio (NHR), monocyte/HDL ratio (MHR), lymphocyte/HDL ratio (LHR), platelet/HDL ratio (PHR) systemic immune-inflammation index (SII), system inflammation response index (SIRI), and aggregate index of systemic inflammation (AISI) have been recently investigated as novel inflammatory markers. Herein, we investigated the correlation between these inflammatory biomarkers and peripheral arterial disease (PAD) in type 2 diabetes mellitus (T2DM) patients. The levels of NHR, MHR, PHR, SII, SIRI and AISI in T2DM-PAD patients were significantly higher than in T2DM-WPAD patients (P < 0.001). The NHR, MHR, PHR, and SIRI were correlated with disease severity, mainly in the Fontaine stages III-IV. Further, multifactorial logistic regression analyses showed that higher NHR, MHR, PHR, SII, SIRI, and AISI were independent risk factors for T2DM-PAD (P < 0.001). The areas under the curve (AUCs) of the NHR, MHR, PHR, SII, SIRI, and AISI for T2DM-PAD patients was 0.703, 0.685, 0.606, 0.648, 0.711, and 0.670, respectively. The AUC of the NHR and SIRI combined model was 0.733. In conclusion,the levels of NHR, MHR, PHR, SII, SIRI, and AISI were higher in T2DM-PAD patients, and NHR, MHR, PHR, and SIRI were independently linked with its clinical severity. The combination model of NHR and SIRI was most valuable for predicting T2DM – PAD.